OP0113 Modification of Salivary Gland Lymphocyte Pattern after Belimumab in Primary Sjogren's Syndrome: Results of the Beliss Study. (23rd January 2014) - Seror, R.; Lazure, T.; Desmoulins, F.; Pavy, S.; Miceli-Richard, C.; Ravaud, P.; Mariette, X.
Abstract : Background: The BAFF (or BLyS) cytokine plays a key role in pathogenesis of primary Sjogren's syndrome (pSS). The level of BAFF is increased in the serum and BAFF may be expressed by salivary epithelial cells and the lymphoid infiltrate of salivary glands. Moreover, BAFF is induced by innate immunity stimulation, the later playing a role in pSS pathogenesis. Belimumab, the first biological treatment inhibiting soluble BAFF/BLyS has proved its effectiveness in systemic lupus and has been recently approved for this indication. Lupus and pSS share a lot of pathogenic mechanism including interferon signature and BAFF involvement. Thus we run the first open label study of belimumab in pSS patients and recently showed that 19/30 patients (63%) achieved the primary end-point which was a composite clinico-biological outcome. Objectives: To address the change in labial salivary gland (LSG) inflammation after Belimumab therapy Methods: Patients were included in 2 parallel and identical studies in 2 European Centres. Patients had to fulfill AECG criteria, to be anti-SSA/SSB positive and had to have at the time of inclusion either systemic complications or early disease (<5 yrs of symptoms), or the presence of biomarker of B-cell activation. The patients were treated with belimumab 10 mg/kg W0, W2, W4 and then every four weeks until W24. Minor labial salivary gland (LSG) biopsies of the 15 patients (all female, mean age=50 yrs, mean disease duration= 5 yrs) from the French center, performed at W0 and W28, were analyzed for estimating the focus score, the B-cell/T-cell ratio (CD20 and CD3 staining), BAFF expression (BAFF (Buffy-2) staining) and NK infiltrate (NKp46 staining). Results: Before treatment, significant lymphocytic sialadenitis (focus score >1) was observed in 11 (78.6%) patients before treatment, five of whom became negative (focus score <1) at w28[51] (p=0.07). The median focus score decreased from 1.6 to 0.5 (p=0.39) and the median Chisholm score from 4 to 2 (p=0.01). B-cell /T cell ratio decreased after treatment in 5 patients and remained stable in all other patients (median ratio decreased from 0.58 to 0.50, p=0.055). Before treatment, a BAFF staining was detected in 11/14 (78.6%) patients, and in only 7/14 (50.0%) after belimumab (p=0.07). The median percentage of BAFF positive cells in foci significantly decreased from 27.5% to 5% after belimumab therapy (p=0.03). NKp46 staining revealed that NK cells infiltrate was predominantly located in interstitium rather than in foci (median number of NK cell: 24.7 vs. 8.2/mm², p=0.0003), and did not change after belimumab. Conclusions: There was a clear tendency in favour of a decrease in foci number, B cells and BAFF-expressing cells within LSG after belimumab therapy. It is tempting to interpret the decrease in BAFF staining as an effect of the drug on membrane BAFF-expressing cells, but it could be also only due to the decrease in B cells expressing BAFF receptors linked to soluble BAFF passively stained by the anti-BAFF antibody. After belimumab therapy, we observed regression of lymphocytic infiltration of LSG in one third of the patients. Also the percentage of BAFF positive cells significantly decreased with a trend to a decrease of B-cell/T-cell ratio. Disclosure of Interest: None Declared